Development of a tool for the evaluation of obesity prevention partnerships. (3rd January 2018) - Indig, Devon; Grunseit, Anne; Greig, Alexandra; Lilley, Helen; Bauman, Adrian
Abstract: Issue addressed: Working in partnership is advocated as a necessary process to achieve shared goals in complex policy areas, yet little effort is dedicated to evaluating how well partnerships are functioning. This study describes the development and psychometric properties of a partnership assessment tool and illustrates its use in an obesity prevention partnership. Methods: A literature scoping review was conducted on existing partnership assessment tools and used to develop a new tool, which was tested using the ACT whole‐of‐government Healthy Weight Initiative at two timepoints. The psychometric properties of the tool were evaluated using principal component analysis and Cronbach's alpha for internal consistency of domain subscales. Results: The review identified 11 partnership assessment tools, from which we identified five domains of partnership to develop the new tool. Factor analysis showed each domain yielded a single subscale. Cronbach's alpha for each of the domain subscales ranged between 0.88 and 0.94 at Timepoint 1 and 0.90 and 0.95 at Timepoint 2 demonstrating very high internal consistency. All subscales demonstrated high correlation with an overall partnership rating, good internal consistency and concordance with issues raised in open‐ended questions. Conclusion: This paper describes the development and implementation of a tool to evaluate partnership functioning, which was found to have high internal consistency and reliability. So what?: With increasing emphasis on working in partnership, using partnership assessment tools can provide useful evidence to assess whether partnerships are a successful strategy in complex programs evaluation.